2017
DOI: 10.15694/mep.2017.000041
|View full text |Cite
|
Sign up to set email alerts
|

Professionalism in Medical Education- Perspectives of Medical Students and Faculty

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 5 publications
0
4
2
Order By: Relevance
“…The current study found that internal motivation is the most important matter as a personal characteristic in medical students' perception regarding medical professionalism, followed by punctuality and attendance. In contrast to earlier findings, a previous study demonstrated honesty, adherence to ethics, and reliability in inpatient care to be the essential items (4) . In the social responsibility category, we found improving access to care to be an essential parameter that goes along with what Rafique et al previously reported (4) .…”
Section: Resultscontrasting
confidence: 89%
See 3 more Smart Citations
“…The current study found that internal motivation is the most important matter as a personal characteristic in medical students' perception regarding medical professionalism, followed by punctuality and attendance. In contrast to earlier findings, a previous study demonstrated honesty, adherence to ethics, and reliability in inpatient care to be the essential items (4) . In the social responsibility category, we found improving access to care to be an essential parameter that goes along with what Rafique et al previously reported (4) .…”
Section: Resultscontrasting
confidence: 89%
“…In contrast to earlier findings, a previous study demonstrated honesty, adherence to ethics, and reliability in inpatient care to be the essential items (4) . In the social responsibility category, we found improving access to care to be an essential parameter that goes along with what Rafique et al previously reported (4) . One exciting finding was to find the respect of other team members as the most ranked factor in interaction with the team.…”
Section: Resultscontrasting
confidence: 89%
See 2 more Smart Citations
“…In Thailand, another study showed that 30% of medical students were clinically depressed, while 12% had suicidal ideation [ 3 ]. We intended to develop a program aimed to optimize not only academic achievement but also professionalism and student well-being [ 4 , 5 ]. Many factors are related to medical students’ academic achievement, mental health problems and well-being.…”
Section: Introductionmentioning
confidence: 99%